Potencial da palha de cana-de-açúcar para produção de etanol - Santos,Fernando A. (2012)
Sugarcane straw biomass accounts for 1/3 of the energy potential of sugarcane and represents a rich source of sugars. Studies have been intensified for the use of this biomass along with bagasse for the production of cellulosic ethanol. Development of this technological path will allow for taking full advantage of sugarcane, increasing ethanol production without expanding the area cultivated. However, in order for this technology to be viable certain challenges must be overcome, including establishment of appropriate conditions of pretreatment and hydrolysis of these materials for release of fermentable sugars.